1998
DOI: 10.1055/s-2008-1058571
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Patients with Chronic Otitis: Indications for Subtotal Petrosectomy and Obliteration of the Middle Ear

Abstract: To date, the rehabilitation of deaf patients with a multichannel cochlear implant has been established as a worldwide accepted method. In case of normal temporal bone anatomy the surgical procedure is standardized and offers few problems. Due to restrictive preoperative patient selection, the incidence of postoperative complications is rather low and is usually flap related.'-5 The percentage of so-called "major complications" which require surgical revision is estimated as low as 7.4%.3 To reduce the surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
1
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 9 publications
3
77
1
9
Order By: Relevance
“…Usually, the inflammation process is eradicated with the result of inflammation-free local circumstances so that an implant loss due to infection or inflammatory reactions can be avoided in most of the cases. A unilateral procedure is only recommended for absolutely inconspicuous and inflammation-free radical cavities [48], [49].…”
Section: Chronic Otitis Mediamentioning
confidence: 99%
“…Usually, the inflammation process is eradicated with the result of inflammation-free local circumstances so that an implant loss due to infection or inflammatory reactions can be avoided in most of the cases. A unilateral procedure is only recommended for absolutely inconspicuous and inflammation-free radical cavities [48], [49].…”
Section: Chronic Otitis Mediamentioning
confidence: 99%
“…In case of a radical cavity after surgical treatment for cholesteatoma, the electrode covered by the epithelial lining of the mastoid will likely become exposed or extruded. Under these circumstances some studies 6,7 ,have shown that the some of the following procedures can be done to protect the electrode. These include subtotal petrosectomy, obliteration of the middle ear cleft with abdominal fat, mastoid obliteration and the blindsac closure of the external ear canal before cochlear implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Subtotal petrosectomy and middle cavity obliteration is another alternative technique for cochlear implantation. This technique can be used, particularly in patients who have chronic otitis media [14] .…”
Section: Discussionmentioning
confidence: 99%